Signal generators for superconducting qubits - Ahmad Faiz Ali (Nanyang Technological University, 2022)
This project explores on the middleware in superconducting processors, specifically that which contributes to quantum control and readouts with the use of microwave signals. Superconducting qubits work in tandem with signals of precise frequency and power. To establish such high quality signals, high quality equipment is required. In particular, a Phase-Locked Oscillator (PLO) manufactured by Renesas, named 8V97003 Evaluation Board (8V97003-EVK in short), that can be programmed using a proprietary downloadable software (Timing Commander ), will be investigated for its performance and reliability in synthesizing adjustable radiofrequency (RF) signals. This project aims to study how the 8V97003-EVK can further optimize and provide versatile and reliable microwave signal sources for quantum experiments in the lab.